Early economic evaluation of an intervention to improve uptake of the NHS England Diabetes Prevention Programme. (3rd April 2022) - Frempong, Samuel N; Shinkins, Bethany; Howdon, Daniel; Messenger, Michael; Neal, Richard D; Sagoo, Gurdeep S
ABSTRACT: Background: Despite reported increases in referral numbers, a large proportion of those with prediabetes still decline participation in the NHS England Diabetes Prevention Programme (NDPP). The aim of this study was to explore whether investment in interventions to improve uptake of the programme has the potential to be cost-effective. Methods: An early cost-utility analysis was conducted using a Markov model parameterized based on secondary data sources. We explored different uptake scenarios and the impact that this had on the maximum allowable intervention price based on cost-effectiveness at the UK NICE willingness to pay threshold of £20, 000 (US 25, 913). Value of information analyses were conducted to explore the potential value of further research to resolve uncertainty at each uptake level. Results: As uptake levels increase, the maximum allowable intervention price and overall expected value of removing decision uncertainty increases. For 5 percentage and 50 percentage points increase in uptake levels, the maximum allowable intervention price is £41.86 (US 54.23) and £418.59 (US 542.34) per person, and the overall expected value of removing decision uncertainty are £361, 818, 839 (US 468, 786, 625) and £1, 468, 712, 316 (US 1, 902, 921, 063) respectively. Conclusion: There is headroom for investment in interventions that improve uptake to the NDPP, thereby allowing the programme itself to be delivered in a manner that remains cost-effective.